Ação e estrutura social em Grounded Theory: Reflexões sobre uma psicologia social sociológica - Bruno Felix von Borell de Araujo; José Luis Álvaro Estramiana (Interamerican Journal of Psychology, 2011)
The objective of this study was to propose ideas for the study of topics involving the interdependence between social contexts and individual action with Grounded Theory. We adopted two strategies: identifying approaches in sociological social psychology that offer ideas about how to study interdependence between social structure and individual action and highlight practical alternatives presented by Grounded Theory theorists to overcome the problem in question. We proposed: a) the adoption of the approaches of Stryker, Giddens, Elias and Bourdieu as sensitizing for developing grounded theories; b) the use and creation of maps or matrices for coding; and c) the confrontation of the substantive theory created with the contributions of the cited theorists in order to situate the theory within the contributions of the scientific community.